2023
DOI: 10.1101/2023.09.24.559170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graph-Dynamo: Learning stochastic cellular state transition dynamics from single cell data

Yan Zhang,
Xiaojie Qiu,
Ke Ni
et al.

Abstract: Modeling cellular processes in the framework of dynamical systems theories is a focused area in systems and mathematical biology, but a bottleneck to extend the efforts to genome-wide modeling is lack of quantitative data to constrain model parameters. With advances of single cell techniques, learning dynamical information from high throughput snapshot single cell data emerges as an exciting direction in single cell studies. Our previously developed dynamo framework reconstructs generally nonlinear genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They applied to EMT datasets and demonstrated that the method recovers gene regulation relations such as activation of SNAIL1 on mesenchymal genes. Separately, Zhang et al also developed a graph Dynamo formalism that describes the full dynamics including convection from the vector field, diffusion from stochastic processes, and cell birth‐death in a multidimensional cell state space (Zhang et al, 2023). Graph Dynamo also uses both the temporal cell density distributions and RNA velocities to constrain model parameters.…”
Section: Unravel Emt Transition Paths Through Snapshot Capture Of Cel...mentioning
confidence: 99%
“…They applied to EMT datasets and demonstrated that the method recovers gene regulation relations such as activation of SNAIL1 on mesenchymal genes. Separately, Zhang et al also developed a graph Dynamo formalism that describes the full dynamics including convection from the vector field, diffusion from stochastic processes, and cell birth‐death in a multidimensional cell state space (Zhang et al, 2023). Graph Dynamo also uses both the temporal cell density distributions and RNA velocities to constrain model parameters.…”
Section: Unravel Emt Transition Paths Through Snapshot Capture Of Cel...mentioning
confidence: 99%